2014
DOI: 10.3402/gha.v7.21292
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and socioeconomic patterns of chronic non-communicable disease among the older adult population in Ghana

Abstract: BackgroundIn Ghana, the older adult population is projected to increase from 5.3% of the total population in 2015 to 8.9% by 2050. National and local governments will need information about non-communicable diseases (NCDs) in this population in order to allocate health system resources and respond to the health needs of older adults.DesignThe 2007/08 Study on global AGEing and adult health (SAGE) Wave 1 in Ghana used face-to-face interviews in a nationally representative sample of persons aged 50-plus years. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
121
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 16 publications
10
121
0
Order By: Relevance
“…In addition, hypertension was measured through physical examinations using a Boso Medistar Wrist BP Monitor Model S (Jungingen, Germany). 12 Previous validation studies indicate that these wrist BP monitoring devices generate accurate measurements especially when the arm is well positioned in relation to the heart. 13 The model has also been validated to the standards of the European Society of Hypertension and that of the International Organization for Standardization 9002.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, hypertension was measured through physical examinations using a Boso Medistar Wrist BP Monitor Model S (Jungingen, Germany). 12 Previous validation studies indicate that these wrist BP monitoring devices generate accurate measurements especially when the arm is well positioned in relation to the heart. 13 The model has also been validated to the standards of the European Society of Hypertension and that of the International Organization for Standardization 9002.…”
Section: Methodsmentioning
confidence: 99%
“…After taking three deep slow breaths, respondents' BP was then measured three times on their left wrists with a minute in between each measurement. 12 BP measurements were performed at the homes of respondents. For the purposes of this study, a respondent was considered hypertensive if the average of the three measurements was ≥140 mm Hg (SBP) or ≥90 mm Hg (DBP) and if the patient self-reported as hypertensive and indicated that they were currently taking antihypertensive medications/treatments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results have shown that more than 28.3% of the study population was aged more than 40 years which according to other studies 37 is one of the non -modifiable risk factors for developing diabetes and hypertension. The total number of participants with a positive family history was not significant which was in contrast to other studies 38,39,40 that showed a positive correlation between family history and the risk of getting diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 71%